2011
DOI: 10.9795/bullgsj.62.105
|View full text |Cite
|
Sign up to set email alerts
|

Laterization of basalts and sandstone associated with the enrichment of Al, Ga and Sc in the Bolaven Plateau, southern Laos

Abstract: This article reports geochemical behavior and enrichment of Al, Ga and Sc by laterization of basalts and sandstone in the Bolaven Plateau, southern Laos. The Bolaven Plateau consists of NeogeneQuaternary basalts and underlying Cretaceous sedimentary rocks. Laterites derived from the basalts and sedimentary rocks are developed on these parent rocks. With increasing the degree of laterization, loss of mobile elements such as Si, alkali elements and alkaline earth elements lead to the enrichment of immobile eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…This result suggests that Sc is relatively immobile and associated with Al or Fe under laterization. Sanematsu et al . (2010) reported a positive linear correlation between Sc and Fe 2 O 3 * contents of basalts, saprolites and laterites in the Bolaven Plateau and that Sc is slightly depleted relative to Fe and Al by strong laterization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This result suggests that Sc is relatively immobile and associated with Al or Fe under laterization. Sanematsu et al . (2010) reported a positive linear correlation between Sc and Fe 2 O 3 * contents of basalts, saprolites and laterites in the Bolaven Plateau and that Sc is slightly depleted relative to Fe and Al by strong laterization.…”
Section: Discussionmentioning
confidence: 99%
“…However Al is mobile by laterization because gibbsite and kaolinite as Al hosts dissolve at a pH < ∼5 (Garrels & Christ, 1965). Sanematsu et al . (2010) reported that Al is remarkably enriched or depleted relative to parent rocks in some horizons of laterite profiles of the Bolaven Plateau.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations